A frequency control strategy of electric vehicles in microgrid using virtual synchronous generator control. (15th December 2019) - Li, Pengfei; Hu, Weihao; Xu, Xiao; Huang, Qi; Liu, Zhou; Chen, Zhe
Abstract: In recent years, with the increase in energy resource penetration into power systems, more technical requirements regarding the frequency control capability of renewable energy have become required. Plug-in electrical vehicles (PEVs) have become increasingly commercialized, and vehicle-to-grid technology has received extensive attention. This paper proposes a novel frequency control strategy for EVs to participate in the primary and secondary frequency regulations of microgrids. Virtual inertia and virtual damping are introduced using a virtual synchronous generator through AC/DC control. Thus, the charging/discharging device has the characteristics of inertia and damping, which are similar to those of a synchronous generator. According to the droop characteristic of an EV's charging frequency, the designed auxiliary frequency regulation method can be used to calculate the power adjustment to change the reference value of the EV's charging/discharging power, allowing the EV to participate in the frequency regulation of a microgrid. The models and connected microgrid were established using MATLAB/Simulink software, and the proposed control strategy was tested. The proposed frequency control strategy can provide virtual inertia, damping, and frequency support; improve the dynamic stability; and realize an effective frequency regulation when the microgrid works in an independent operational mode. Highlights: The AC/DC converter uses the VSG to provide inertia support for microgrid. The strategy uses power adjustment to change charging power for frequency control. Primary and secondary frequency regulation can be realized by designed strategy. The method improves dynamic stability and frequency control of microgrid.